THE METHOD OF MULTI-CRITERIA EVALUATING SOFTWARE COMPLIANCE WITH THE CUSTOMER’S REQUIREMENTS - Писарчук, О. О.; Безкоровайна, Ю. М.; Дишлевий, О. П.; Скалова, В. А. (Science-based technologies, 2019)
Software development is divided into separate stages. They determine the model of the software life cycle, such as requirements definition, design, construction or coding, testing, checking for compliance, performance or implementation software. Each stage of software development has its own problems. The article describes the stage of evaluation release and compliance with the customer’s requirements For evaluation using qualitative and quantitative characteristics - metrics. It is necessary to calculate the values of metrics for making a decision for software production with maintenance. Traditional approaches to software evaluation do not provide an integrated assessment. It requires subjective analysis of the branched system of partial indicators, which to varying degrees reflect the degree of developed software to the requirements of the customer. The purpose of the article is to develop an evaluating method of using multi-criteria evaluating. During the research the mathematical optimization model for evaluating the compliance of software with the requirements of the customer has been improved. The model differs from known analogs using the proposed system factors, indicators and performance criteria. It takes into account a set of conflicting partial criteria, divided into two groups belonging to a certain category of performance. As a result of the assessment, the technology of nested convolutions was applied. The formation of the model is based on the use of methods for solving multi-criteria problems, in particular, the method of reducing it to a single-criteria form by convoluting partial criteria. An example of the use of the developed model confirmed its suitability for solving practical problems of estimation.